Sustainable Development Goals (SDGs) and antibiotic resistance: the need to search beyond - Riya, Jannatul Ferdous Islam (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.